Effect of milk replacers on growth curves up to 90 days old in developing Siboney de Cuba females - Alonso, A. C.; Soto, L. D.; Chongo, Bertha; Torres, Verena; Zamora, A. (Cuban Journal of Agricultural Science, 2016)
Under production conditions, the effect of two technologies of milk replacers on growth curves (up to 90 days) of developing Siboney de Cuba females was evaluated. For that purpose, 30 females were used, randomly divided, at their arrival to the rearing unit, into two groups (15 animals each). For growth analysis, linear (linear, square linear and square logarithmic models) and non-linear (logistic, Gompertz and Richards) regression models were tested. For linear models, gains wereestimated by the least square method. For non-linear ones, the interactive method of Marquardt was applied. The best adjustmentwas determined from different statistical criteria. ANOVA was applied for weights and daily mean gains, reached in different moments. The square logarithmic model had the best fit of growth, with R2 => 0.93 and P < 0.001 in both treatments, from which the performance of liveweight increase in other group of animals may be predicted, with the use of similar combinations per treatment. Daily mean gain and liveweight, up to 90 d, differed in both treatments after a month of birth. For females of the second treatment, daily mean gains were near 500 g/animal/d, and liveweight was around 69.2 kg up to weaning.Key words: milk replacers, growth curves, Siboney de Cuba females